2017
DOI: 10.1186/s40199-017-0169-x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of memory and learning by intracerebroventricular microinjection of T3 in rat model of ischemic brain stroke mediated by upregulation of BDNF and GDNF in CA1 hippocampal region

Abstract: BackgroundIschemic stroke is a common leading cause of death and disability with lack of effective therapies. In this study, T3 was intra-ventricularly injected to evaluate gene expression and protein concentration of and brain-derived neurotrophic factor (BDNF) and Glial cell-derived neurotrophic factor (GDNF) in hippocampal CA1 region in rat model of brain ischemia/reperfusion (I/R).MethodsIn this study, transient middle cerebral artery occlusion (tMCAo) was used as model of ischemic brain stroke. Rats were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 55 publications
1
37
0
Order By: Relevance
“…23 Our results showed that MCAO caused an increase in the infarct size as compared with the sham group, the histopathological examination revealed edema, increase in the cellular permeability as well as infiltration of inflammatory cells. Global ischemia is produced by transient bilateral carotid artery stenosis, while focal ischemia is produced by transient MCAO.…”
Section: Discussionmentioning
confidence: 46%
“…23 Our results showed that MCAO caused an increase in the infarct size as compared with the sham group, the histopathological examination revealed edema, increase in the cellular permeability as well as infiltration of inflammatory cells. Global ischemia is produced by transient bilateral carotid artery stenosis, while focal ischemia is produced by transient MCAO.…”
Section: Discussionmentioning
confidence: 46%
“…Several fundamental studies previously explored the possible mechanisms underlying the prognostic role of thyroid hormones in AIS. Some experiments found that exogenous T3 and T4 elevated the concentrations of certain important neuroprotective agents, such as brain-derived neurotrophic factor (BDNF) and glial cell-derived neurotrophic factor (GDNF), in a rat model of brain ischemia/reperfusion 32 35 . Two studies reported evident reductions of tissue infarction and edema in a transient middle cerebral artery occlusion (t-MCAO) model of male mice injected with T3, and attributed this anti-edema effect to suppression of the expression of aquaporin-4 (AQP4) water channels by T3 36 , 37 .…”
Section: Discussionmentioning
confidence: 99%
“…- Sabbaghziarani et al 2017: similar to previous study from Mokhtari et al (2017), here cerebral ischemia was induced by MCAo in male Wistar rats; a group of rats was also injected with T3 (25 μg/kg, IV injection) at 24 hours after ischemia. BDNF gene and protein levels (along with nestin and Sox2) were increased upon T3 treatment vs ischemic group.…”
Section: Empirical Evidencementioning
confidence: 81%
“…- Mokhtari et al 2017: in this in vivo study rats underwent transient middle cerebral artery occlusion (tMCAo) to induce ischemic brain stroke. Rats were randomly divided in four groups: Co (control), Sh (sham), tMCAo and tMCAo + T3 (intracerebroventricular injection of T3 at 25 ug/kg body administered 24 after reperfusion).…”
Section: Empirical Evidencementioning
confidence: 99%